RELIABILITY, VALIDITY AND SENSITIVITY OF RUSSIAN VERSIONS OF PEDSQL GENERIC CORE SCALE AND PEDSQL RHEUMATOLOGY MODULE QUESTIONNAIRES - R.V. Denisova; E.I. Alexeeva; V.Yu. Al'bitsky; I.V. Vinyarskaya; S.I. Valieva; T.M. Bzarova; A.O. Lisitsin; E.Yu. Gudkova (Вопросы современной педиатрии)
The article presents a results of evaluation of psychometric properties of Russian versions of PedsQL Rheumatology Module (PedsQL RM) and PedsQL Generic Core Scale (PedsQL GCS) questionnaires in estimation of quality of life in children of 5-18 years old with juvenile arthritis.138 children took part in this trial: 57 patients in age 5-7 years old (middle age 5.86±0.88 years old), 43 – from 8 to 12 years old (middle age 9.69±0.88 years old), and 38 children – from 13 to 18 years old (middle age 13.8±1.03 years old). Estimation of reliability of questionnaires was held with calculation of Cronbach's alpha, constructive validity – with method of “known groups” with the help of analysis of dependence of quality of life indices from index of functional insufficiency (estimated by CHAQ questionnaire). Evaluation of sensitivity was carried out with comparison of quality of life in children (n=24, n=16, n=14) at the initial stage and on 6-th week of treatment with infliximab. Cronbach’s alpha was 0.70-0.91, which testifies to high reliability of Russian versions of PedsQL RM and PedsQL GCS questionnaires. Significant inverse negative relationship of functional insufficiency index reflects validity of Russian versions of PedsQL RM and PedsQL GCS questionnaires. Improvement of quality of life in children with rheumatoid arthritis confirms high sensitivity of Russian versions of PedsQL RM and PedsQL GCS questionnaires. Thus, Russian versions of PedsQL RM and PedsQL GCS questionnaires allow impartial estimation of quality of life in children with juvenile arthritis.Key words: juvenile arthritis, children, quality of life, PedsQL Rheumatology Module and PedsQL Generic Core Scale, infliximab.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(1):30-40)